1992
DOI: 10.1002/ajp.1350270402
|View full text |Cite
|
Sign up to set email alerts
|

Dialects in wild chimpanzees?

Abstract: Chimpanzees emit a loud, species-typical long distance call known as the pant hoot. Geographic variation between the pant hoots of chimpanzees living in two neighboring populations, the Mahale Mountains and Gombe Stream National Parks, Tanzania, was examined. Analysis of six acoustic features revealed subtle differences in the way chimpanzees from the two populations called. Individuals from the Mahale study site uttered one section of their pant hoots at a faster rate and with shorter elements than animals fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
135
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(148 citation statements)
references
References 20 publications
4
135
3
Order By: Relevance
“…Accumulating evidence of call convergence (the convergence of the acoustic features of a call to a shared structure) within social groups suggests some degree of vocal plasticity in nonhuman primates (Fischer et al, 1998;Gouzoules and Gouzoules, 1990;Mitani et al, 1992) (reviewed by Egnor and Hauser, 2004). This conclusion is still controversial; many investigators argue that the observed convergence may be the result of shared motivational states, shared genetics, shared environment or the selection of a specific call from within an innately determined repertoire (Janik and Slater, 2000;Lieblich et al, 1980;Mitani et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence of call convergence (the convergence of the acoustic features of a call to a shared structure) within social groups suggests some degree of vocal plasticity in nonhuman primates (Fischer et al, 1998;Gouzoules and Gouzoules, 1990;Mitani et al, 1992) (reviewed by Egnor and Hauser, 2004). This conclusion is still controversial; many investigators argue that the observed convergence may be the result of shared motivational states, shared genetics, shared environment or the selection of a specific call from within an innately determined repertoire (Janik and Slater, 2000;Lieblich et al, 1980;Mitani et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is still controversial; many investigators argue that the observed convergence may be the result of shared motivational states, shared genetics, shared environment or the selection of a specific call from within an innately determined repertoire (Janik and Slater, 2000;Lieblich et al, 1980;Mitani et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…This situation is common, where studies find geographical differences in calls but are not able to distinguish between possible inherited and learned components in call development (e.g. Wang Ding et al 1995, Mitani et al 1992, Green 1975. In some cases, the calls of hybrids can help.…”
Section: Methods Used To Study Vocal Learningmentioning
confidence: 99%
“…For example, early papers on geographical variation in pant hoots of chimpanzees (Pan troglodytes) suggested that this variation was evidence for production learning in this species (Mitani et al 1992;Mitani and Brandt 1994;Clark Arcadi 1996). Mitani et al (1999) reassessed the interpretation of geographical variation in chimpanzee calls.…”
Section: Geographical and Temporal Variation In Callsmentioning
confidence: 99%